Aktivitas dan Motivasi Belajar Matematika Melalui Model Pembelajaran Kooperatif Tipe Think Pair Square - Aprisa Nilam Sari; Tasnim Rahmat; Isnaniah, Isnaniah; M. Imamuddin (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to determine the activity and motivation of students learning mathematics using the Think Pair Square cooperative learning model is better than conventional learning. This type of research is an experiment with a research design namely The Static Group Comparison Design. The population in this study were all students, where there are 10 classes with a total of 318 students. Sampling was done randomly first conducted a normality test and homogeneity test on the population data. The sample in this study was class VIII. I as the experimental class and VIII. J as the control class. The instruments used were a mathematics learning motivation questionnaire and a learning activity observation sheet. The results of the activity observation sheet were analyzed using the percentage of activity, after calculating the activity score, an overall average of 82.3% was obtained with active criteria. Meanwhile, the results of the calculation of the data analysis of the students' mathematics learning motivation questionnaire at the real level using the t-test, obtained t count 2.033400708 and t table 1.998971517 where t count > t table. Meanwhile, using SPSS, sig = 0.034 is obtained, meaning significant <a with a real level, based on these results, accept H1 and reject H0. So, it can be concluded that students' mathematics learning activities and motivation using the Think Pair Square type of cooperative learning model are better than conventional learning.